2021
DOI: 10.1016/j.stem.2021.04.028
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 infects human adult donor eyes and hESC-derived ocular epithelium

Abstract: The SARS-CoV-2 pandemic has caused unparalleled disruption of global behavior and significant loss of life. To minimize SARS-CoV-2 spread, understanding the mechanisms of infection from all possible routes of entry is essential. While aerosol transmission is thought to be the primary route of spread, viral particles have been detected in ocular fluid suggesting the eye may be a vulnerable point of viral entry. To this end, we confirmed SARS-CoV-2 entry factor and antigen expression in post-mortem COVID-19 pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
50
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 53 publications
(54 citation statements)
references
References 61 publications
4
50
0
Order By: Relevance
“…It may be questioned if such a low ACE2 expression is relevant for SARS-CoV-2 infection. It has to be noted, that some occasional expression of ACE2 immunoreactivity was detected in the ocular surface and lacrimal system, including a small spot in the limbal epithelium of a single conjunctiva similar to an earlier report 37 and some parts of glandular tissue of some lacrimal gland specimens that showed weak staining. Although there is few evidence so far, it remains to be clarified whether individual factors such as genetic predisposition, inflammation or hypoxia can trigger ACE2 expression in the ocular surface and may be responsible for the observed occasional and localised ACE2 expression 10 , 12 , 29 , 38 .…”
Section: Discussionsupporting
confidence: 82%
“…It may be questioned if such a low ACE2 expression is relevant for SARS-CoV-2 infection. It has to be noted, that some occasional expression of ACE2 immunoreactivity was detected in the ocular surface and lacrimal system, including a small spot in the limbal epithelium of a single conjunctiva similar to an earlier report 37 and some parts of glandular tissue of some lacrimal gland specimens that showed weak staining. Although there is few evidence so far, it remains to be clarified whether individual factors such as genetic predisposition, inflammation or hypoxia can trigger ACE2 expression in the ocular surface and may be responsible for the observed occasional and localised ACE2 expression 10 , 12 , 29 , 38 .…”
Section: Discussionsupporting
confidence: 82%
“…The former refers to the direct myocardial invasion of SARS-CoV-2 into the heart tissue mediated by angiotensin-converting enzyme 2 (ACE2), and the latter is either a cytokine storm or hypoxia-induced cardiac myocyte apoptosis [4] . Histopathological studies have reported organotropism of SARS-CoV-2 beyond the respiratory tract, including renal, myocardial, neurologic, pharyngeal, gastrointestinal and ocular tissues; the pathophysiology underlying cardiovascular manifestations is probably multifactorial [ 5 , 8 ]. ACE2 is highly expressed in cardiovascular tissues, including cardiac myocytes, fibroblasts, endothelial cells, and smooth muscle cells [ 6 , 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the transcriptional footprint of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection also indicates significant interference imposed on host biology as it relates to the response to virus infection. While SARS-CoV-2-infected cells do demonstrate a diminished IFN-I response as a result of a number of virus-specific products reported to antagonize PAMP detection, the infection seemingly demonstrates high levels of NF-κB activation for reasons that remain unclear (14,15). This process of SARS-CoV-2 partially blocking the host innate response results in a lack of local replication control alongside high level of proinflammatory cytokines and chemokines which may constitute the molecular basis of coronavirus disease-2019-ultimately CORONAVIRUS Immune memory from SARS-CoV-2 infection in hamsters provides variant-independent protection but still allows virus transmission (Page numbers not final at time of first release) 2 resulting in COVID-19.…”
Section: Introductionmentioning
confidence: 99%